2016
DOI: 10.1097/tp.0000000000000920
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Live Kidney Donors Who Develop End-Stage Renal Disease

Abstract: Background Kidney donors can develop ESRD after donation, but the outcomes of those who do remain poorly characterized. Methods Using USRDS and SRTR data, we compared access to kidney transplantation (KT), time from ESRD to listing, time from listing to KT, and post-KT graft failure and death between donors and matched nondonors with ESRD. Results Among 99 donors between April 1994 and November 2011 who developed ESRD, 78 initially received dialysis (of whom 37 listed for KT, 2 received live donor KT witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
0
18
0
Order By: Relevance
“…Even if the OPTN database were complete, we would emphasize that an accurate analysis of donor ESRD (and any potential links to recipient ESRD causes) should tally all donors with ESRD regardless of treatment modality (transplant, dialysis, and no treatment), ideally including those without access to care and those who donated in the United States but live overseas. Because these harder-to-reach donors may also be more vulnerable (poorer and more geographically remote), their outcomes are particularly relevant in order to understand and discuss the risk of developing ESRD postdonation (22). Although some of this information can be obtained by combining searches from other databases, the ideal solution is the establishment of a national donor database (23).…”
Section: Discussionmentioning
confidence: 99%
“…Even if the OPTN database were complete, we would emphasize that an accurate analysis of donor ESRD (and any potential links to recipient ESRD causes) should tally all donors with ESRD regardless of treatment modality (transplant, dialysis, and no treatment), ideally including those without access to care and those who donated in the United States but live overseas. Because these harder-to-reach donors may also be more vulnerable (poorer and more geographically remote), their outcomes are particularly relevant in order to understand and discuss the risk of developing ESRD postdonation (22). Although some of this information can be obtained by combining searches from other databases, the ideal solution is the establishment of a national donor database (23).…”
Section: Discussionmentioning
confidence: 99%
“…groups have reported a higher risk of ESRD on long-term follow-up in donors when compared to healthy control population who would have been eligible for kidney donation 28,29. In a subgroup analysis of >60-years-old, Muzaale et al reported a cumulative ESRD incidence of 70.2 (95% CI, 30.4-161.8) per 10 000 at 15 years postdonation, which was higher than that for younger donors.…”
mentioning
confidence: 98%
“…Last, in the US context, we recommend that the counseling of donors about the small increased risk of kidney failure after donation should also include information about former donors receiving very high priority in the deceased donor list in the unlikely event that they develop kidney failure. 23,24 Compatibility…”
Section: Commentarymentioning
confidence: 99%